Rediscovery of Hymenocallis cordifolia (Hymenocallideae, Amaryllidaceae) an endemic species of Guerrero, Mexico - Aguirre-León, Ernesto; Espejo-Serna, Adolfo; López-Ferrari, Ana Rosa (Phytotaxa, 2026)
A complete description and a detailed figure of Hymenocallis cordifolia, a rare, microendemic species of the state of Guerrero, Mexico, are provided. The taxon is distinguished from all the other species of the genus by the presence of broadly ovate leaves whose leaf sheaths form a long and conspicuous pseudostem. An epitype is designated. Until now, there was no reference herbarium material of the species in any Mexican collection, nor was there any data regarding its phenology and distribution.